Perception and contributing factors to medication administration errors among nurses in Nigeria - Mary Oyenike Ayorinde; Peter Ibukunoluwa Alabi (Elsevier, 2019)
Purpose: The study assessed perception and contributing factors to medication administration errors among nurses. Design: A quantitative descriptive design was adopted. Three hundred nurses participated in the study during the month of July 2015. A self-administered questionnaire was used to obtain information on registered nurses characteristics, knowledge and perceived causes of medication admiration errors. Descriptive analysis and inferential statistics were done using Statistical Package for Social Sciences. Results: The findings of the study revealed that Nurses have good knowledge and perception of medication administration errors. Confusion of drugs with different names and increase patient to nurse staffing ratio constitute the major contributing factors for the occurrence of medication administration error among them. Furthermore, majority of the nurses are aware of guidelines and methods to follow to prevent the occurrence of medication administration errors. Conclusion: In this regards, identification of the main factors contributing to medication administration errors allows nurses and system to eliminate situations such as nurse staffing, medication transcribing issues, poor physician communication, problem with medication packaging and poor reporting system as well as incorporating changes that minimize them. Also, nursing supervisors should create an enabling environment which allows incidence of medication administration errors to be reported not on the basis of being punished but to initiate actions to prevent future occurrences. This will improve and enhance patient safety environment in the hospital. Keywords: Perception, Medication administration error, Contributing factor, Nurse